Multi-metal oxycarbide ion storage layer material for electrochromic device and preparation method of multi-metal oxycarbide ion storage layer material
By using a polymetallic carbon oxide ion storage layer material in an electrochromic device, combining the combination of vanadium oxide with a second metal or non-metal oxide precursor, the problem of poor stability of vanadium pentoxide at high temperatures is solved. Excellent charge and discharge cycle stability and color distortion response speed are achieved.
Patent Information
- Application Number
- CN202411427251.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-18
AI Technical Summary
Vanadium pentoxide has poor charging and discharge cycle stability in electrochromic devices, especially failure at high temperatures, which affects device reliability. At the same time, doping metal heteroatoms can improve stability but reduce the discoloration response speed.
Using polymetallic carbon oxide ion storage layer material, the ion storage layer of nanoparticles is prepared by combining the vanadium oxide precursor with the second metal or non-metal oxide precursor, and aged treatment and baking in sections to form an ion storage layer of nanoparticles. Material.
It significantly improves the charge and discharge cycle stability of vanadium pentoxide, while maintaining a faster color discoloration response speed, and is suitable for large-scale precision coating roll-to-roll production.
Smart Images

Figure CN119472121A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multi-metal carbon oxide ion storage layer material for an electrochromic device and a preparation method thereof, belonging to the technical field of inorganic metal oxide thin films. Background Art
[0002] Electrochromic devices are usually composed of a transparent conductive layer (ITO), an electrochromic functional layer, an electrolyte layer, an ion storage layer and a transparent conductive layer (ITO). The working principle of the ion storage layer is to undergo a reversible electrochemical reaction, and to cooperate with the electrochromic layer to insert or remove counterions to complete forward or reverse reversible color change. In the process of inserting and removing counterions, the ion storage layer will undergo changes in chemical structure and volume, which has a relatively large impact on the charge and discharge cycle stability of the material. Vanadium pentoxide, as an oxide with a layered structure, is often used as an electrochromic material or ion storage material in many reported studies, but it has the problem of poor cycle stability, especially at high temperatures, it will quickly fail, which seriously affects the reliability of electrochromic devices. The charge and discharge cycle stability can be improved by doping with some metal heteroatoms, but it will cause the color change response speed to slow down. Therefore, it is necessary to develop a method to enable functional materials based on vanadium pentoxide to have both excellent charge and discharge cycle stability and color change response speed. Summary of the invention
[0003] In order to overcome the defects and shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a multi-metal carbon oxide ion storage layer material for an electrochromic device and a preparation method thereof; the multi-metal carbon oxide composition provided by the present invention, when used as an ion storage layer, can significantly improve the charge and discharge cycle stability of vanadium pentoxide, and at the same time has a good color change response speed.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0005] In a first aspect, the present invention provides a multi-metal carbide ion storage layer material for an electrochromic device, wherein the ion storage layer material is prepared by subjecting a multi-metal carbide precursor composition to an aging treatment and then adopting a wet coating method, and the composition comprises a first metal oxide precursor, a second metal and / or non-metal oxide precursor and a polar solvent.
[0006] Further, the first metal oxide precursor is a vanadium oxide precursor, and the vanadium oxide precursor includes alkoxy vanadium oxide and / or alkoxy vanadium;
[0007] The vanadium oxide precursor is selected from at least one of trimethoxy vanadium oxide (V), ethoxide vanadium (V), triethoxy vanadium oxide (V), triisopropoxy vanadium oxide (V), tri-n-butoxy vanadium oxide (V), tri-tert-butoxy vanadium oxide (V), isopropoxy acetylacetonate vanadium (V) (V(acac)(O-iPr)4, V(acac)2(O-iPr)3, V(acac)3(O-iPr)2, V(acac)4(O-iPr)), and vanadium (IV) oxide diacetylacetonate.
[0008] Furthermore, the second metal or non-metal oxide precursor is selected from at least one of a titanium oxide precursor, a niobium oxide precursor, a zirconium oxide precursor and a silicon oxide precursor.
[0009] Further, the titanium oxide precursor is selected from at least one of tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate, acetylacetonato titanium and bis(acetylacetonato) diisopropyl titanate;
[0010] The niobium oxide precursor is selected from at least one of niobium isopropoxide, niobium n-propoxide, niobium n-butoxide, niobium ethoxide and niobium oxalate;
[0011] The zirconium oxide precursor is selected from at least one of tetrabutyl zirconate, tetraisopropyl zirconate, tetraethyl zirconate, zirconium acetate and zirconium acetylacetonate;
[0012] The silicon oxide precursor is selected from at least one of alkoxy-containing silanes (such as tetraethoxysilane, tetramethoxysilane), hydroxy-containing silanes, mercapto-containing silanes, epoxy-containing silanes and fluorine-containing silanes.
[0013] Furthermore, the polar solvent is selected from alcohol solvents and / or ketone solvents.
[0014] Furthermore, the polar solvent is selected from at least one of ethanol, isopropanol, n-butanol, sec-butanol and butanone.
[0015] Furthermore, the aging treatment comprises: stirring the prepared composition in a constant humidity environment with a humidity of 30-75Rh% at room temperature for 2-24 hours in an open state, then sealing the composition with a cover, and leaving it to stand at room temperature for 3-14 days.
[0016] And / or, the concentration of the precursor in the composition is 1-30 wt %.
[0017] In the present invention, during the aging process, the oxide precursors in the system react and condense with each other to form a nanoparticle sol.
[0018] Furthermore, the ion storage layer material includes one or more of titanium oxide, niobium oxide, zirconium oxide, silicon oxide, and multi-metal carbon oxide or hydrate materials doped with vanadium oxide.
[0019] More preferably, the ion storage layer material comprises a multi-metal oxycarbide hydrate material doped with vanadium oxide, selected from the group consisting of titanium oxide, niobium oxide, zirconium oxide and silicon oxide.
[0020] Furthermore, the ion storage layer material includes but is not limited to at least one of the following multi-metal carbon oxides:
[0021] Ti x1 V x2 O y C z nH2O, wherein the ratio (molar ratio) of x1 / x2 is 1:10 to 1:1;
[0022] Nb x1 V x2 O y C z ●nH2O, where the ratio of x1 / x2 is 1:20 to 1:1;
[0023] Zr x1 V x2 O y C z ●nH2O, where the ratio of x1 / x2 is 1:10 to 1:1;
[0024] Si x1 V x2 O y C z ●nH2O, where the ratio of x1 / x2 is 1:15 to 1:2;
[0025] Si x1 Ti x2 V x3 O y C z ●nH2O, where the ratio of x1 / x2 is 1:15 to 1:1, and the ratio of x2 / x3 is 1:10 to 1:1;
[0026] In the above-mentioned polymetallic carbide, n is 0-3.
[0027] More preferably, n in the multi-metal oxycarbide is not 0.
[0028] Furthermore, in the polymetallic carbide, the atomic ratio of tetravalent vanadium to vanadium element is 10-70 at%. In the present invention, the tetravalent vanadium may be derived from the formation of oxygen vacancies caused by heteroatom doping, or from the redox reaction between the vanadium oxide precursor (pentavalent vanadium) and the organic solvent (alcohol solvent and / or ketone solvent) during the aging process.
[0029] Furthermore, it comprises a coating layer with a thickness of 20-300 nm, and the ion storage layer material exists in the coating layer in the form of nanoparticle accumulation with a particle size of 10-50 nm.
[0030] In a second aspect, the present invention provides an electrochromic device, comprising the ion storage layer material described in the first aspect.
[0031] In a third aspect, the present invention provides a method for preparing the above-mentioned ion storage layer material, comprising: providing a multi-metal carbide precursor composition for preparing the ion storage layer material; coating the composition into a film on a conductive substrate after aging treatment, and then subjecting the composition to a staged baking treatment to obtain the final multi-metal carbide ion storage layer material.
[0032] Furthermore, the conductive substrate includes PET-ITO film, ITO conductive glass, PET-metal grid or PET-nanosilver wire film.
[0033] Furthermore, the coating and film formation includes coating and film formation by spin coating, screen printing, micro gravure coating or slit coating.
[0034] Furthermore, the segmented baking includes two stages of baking: low temperature and high temperature; the temperature of the low temperature baking is 30-50°C, the time is 1-5 minutes, and the temperature of the high temperature baking is 100-145°C, the time is 2-60 minutes.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention adopts a second metal or non-metal oxide precursor to dope a vanadium oxide precursor, and after simple aging treatment and segmented baking, under the condition of adjusting the proportion of each component, a hydrated multi-metal carbon oxide ion storage layer material with excellent performance can be obtained. Compared with vanadium oxide as an ion storage layer, the electrochromic device prepared maintains an excellent color change response speed while its charge and discharge cycle stability is significantly improved; in addition, the preparation method of the present invention is simple, the baking temperature is low, and it can be adapted to large-scale roll-to-roll production of precision coating, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The ion storage capacity per unit area of the electrochromic devices prepared in the examples and comparative examples under high temperature conditions of 80°C varies with the number of charge and discharge cycles;
[0038] Figure 2 The color change response time of the electrochromic devices prepared in the examples and comparative examples at room temperature (dark state to bright state T90+, bright state to dark state T90-);
[0039] Figure 3 is Ti in Example 1x1 V x2 O y C z ●Surface electron microscope morphology of nH2O ion storage layer material;
[0040] Figure 4 This is a surface electron microscope morphology image of the ion storage layer material prepared from a single vanadium oxide precursor in Comparative Example 1;
[0041] Figure 5 This is an example of the X-ray photoelectron spectrum and valence state fitting diagram of vanadium 2p in the multi-metal carbon oxide ion storage layer material. DETAILED DESCRIPTION
[0042] For ease of understanding, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to explain the present invention and are not used to limit the scope of the present invention.
[0043] The present disclosure also relates to an electrochromic device comprising a charge storage material as described herein as a main functional layer. Other components of the electrochromic device are generally known in the art, such as the electrochromic device involved in the following embodiments further comprising an electrochromic polymer as described in U.S. Patent No. 9975989, which is incorporated herein by reference in its entirety; and an electrolyte layer as described in U.S. Patent No. 0299932, which is incorporated herein by reference in its entirety.
[0044] Example 1: Ti x1 V x2 O y C z ●Preparation of nH2O ion storage layer
[0045] Weigh 34g of n-butanol solvent, add it to a 100ml sample bottle, turn on magnetic stirring, then weigh 5.01g of tributoxyvanadium oxide and 0.99g of tetrabutyl titanate and add them to the n-butanol solvent (x2 / x1=6:1), stir open for 4h at room temperature and humidity 65Rh%, then seal it with a cover, and let it stand at room temperature for 7 days to obtain an ion storage material precursor solution. The prepared solution is coated on a PET film with indium tin oxide (ITO) sputtered on the surface with an OSP-12 wire rod at a coating speed of 400mm / min, then baked in a 32℃ oven for 3min to remove most of the solvent, and then transferred to a 140℃ oven for baking for 5min to obtain the final Ti x1 V x2 O y C z ●nH2O ion storage layer membrane. The surface microstructure of the prepared ion storage membrane is as follows Figure 3As shown, the nanoparticles of 10-20 nm are piled up and partially connected. The tetravalent vanadium content in the prepared ion storage layer material is 37.2 at%.
[0046] Example 2: Nb x1 V x2 O y C z ●Preparation of nH2O ion storage layer
[0047] Weigh 34g of n-butanol solvent, add it to a 100ml sample bottle, turn on magnetic stirring, then weigh 4.28g of vanadium tris-butoxide and 1.72g of niobium n-butoxide and add them to the n-butanol solvent (x2 / x1=4:1), stir them open for 4h at room temperature and humidity 65Rh%, then seal them, and let them stand at room temperature for 10 days to obtain an ion storage material precursor solution. The prepared solution is coated on a PET film with indium tin oxide (ITO) sputtered on the surface with an OSP-12 wire rod at a coating speed of 400mm / min, then baked in a 32℃ oven for 3min to remove most of the solvent, and then transferred to a 130℃ oven for baking for 5min to obtain the final Nb x1 V x2 O y C z ●nH2O ion storage layer film. The tetravalent vanadium content in the prepared ion storage layer material is 25.6at%.
[0048] Example 3: Zr x1 V x2 O y C z ●Preparation of nH2O ion storage layer
[0049] Weigh 34g of n-butanol solvent, add it to a 100ml sample bottle, turn on magnetic stirring, then weigh 4.49g of tri-butoxy vanadium oxide and 1.51g of tetrabutyl zirconate and add them to the n-butanol solvent (x2 / x1=4:1), stir open for 2h at room temperature and humidity 65Rh%, then seal it, and let it stand at room temperature for 7 days to obtain an ion storage material precursor solution. The prepared solution is coated on a PET film with indium tin oxide (ITO) sputtered on the surface with an OSP-12 wire rod at a coating speed of 400mm / min, then baked in a 32℃ oven for 3min to remove most of the solvent, and then transferred to a 140℃ oven for baking for 5min to obtain the final Zr x1 V x2 O y C z ●nH2O ion storage layer film. The tetravalent vanadium content of the prepared ion storage layer material is 41.2 at%.
[0050] Example 4: Six1 V x2 O y C z ●Preparation of nH2O ion storage layer
[0051] Weigh 34g of ethanol solvent, add it to a 100ml sample bottle, turn on magnetic stirring, then weigh 5.12g of triethoxyvanadium oxide and 0.88g of tetraethoxysilane and add them to the n-butanol solvent (x2 / x1=6:1), cover and seal, stir at room temperature for 1h to obtain the ion storage material precursor solution. The prepared solution is coated on a PET film with indium tin oxide (ITO) sputtered on the surface with an OSP-12 wire rod at a coating speed of 400mm / min, then baked in a 32℃ oven for 3min to remove most of the solvent, and then transferred to a 120℃ oven for baking for 5min to obtain the final Si x1 V x2 O y C z ●nH2O ion storage layer film. The tetravalent vanadium content in the prepared ion storage layer material is 29.8at%.
[0052] Example 5: Si x1 Ti x2 V x3 O y C z ●Preparation of nH2O ion storage layer
[0053] Weigh 34g of n-butanol solvent, add it to a 100ml sample bottle, turn on magnetic stirring, then weigh 4.33g of tributoxyvanadium oxide, 1.28g of tetrabutyl titanate, and 0.39g of tetraethoxysilane and add them to the n-butanol solvent (x3 / x2 / x1=1:2:8), stir open for 4h at room temperature and humidity 65Rh%, then seal it with a cover, and let it stand at room temperature for 7 days to obtain an ion storage material precursor solution. The prepared solution is coated on a PET film with indium tin oxide (ITO) sputtered on the surface with an OSP-12 wire rod at a coating speed of 400mm / min, then baked in a 32℃ oven for 3min to remove most of the solvent, and then transferred to a 140℃ oven for baking for 5min to obtain the final Si x1 Ti x2 V x3 O y C z ●nH2O ion storage layer film. The tetravalent vanadium content of the prepared ion storage layer material is 39.7at%.
[0054] Comparative Example 1: Preparation of vanadium oxide ion storage layer
[0055] Weigh 34g of n-butanol solvent, add it to a 100ml sample bottle, turn on magnetic stirring, then weigh 6g of tributoxy vanadium oxide and add it to the n-butanol solvent, stir it open for 4h at room temperature and humidity 65Rh%, then seal it with a cover, and let it stand at room temperature for 7 days. The prepared solution is coated on a PET film with indium tin oxide (ITO) sputtered on the surface using an OSP-12 wire rod at a coating speed of 400mm / min, and then baked in a 32°C oven for 3min to remove most of the solvent, and then transferred to a 140°C oven and baked for 5min to obtain the final vanadium oxide ion storage layer membrane. The surface micromorphology of the prepared ion storage membrane is as follows Figure 4 As shown, the tetravalent vanadium content in the prepared ion storage material is 7.3 at%.
[0056] Comparative Example 2: Ti x1 V x2 O y C z Preparation of ion storage layer
[0057] The difference from Example 1 is that no aging treatment is performed.
[0058] Weigh 34g of n-butanol solvent, add it to a 100ml sample bottle, turn on magnetic stirring, then weigh 5.01g of tributoxyvanadium oxide and 0.99g of tetrabutyl titanate and add them to the n-butanol solvent (x2 / x1=6:1), stir in a closed container for 1h, and then coat the prepared solution on a PET film sputtered with indium tin oxide (ITO) on the surface with an OSP-12 wire rod at a coating speed of 400mm / min, and then bake it in a 32°C oven for 3min to remove most of the solvent, and then transfer it to a 140°C oven and bake it for 5min to obtain the final Ti x1 V x2 O y C z Ion storage layer membrane. The tetravalent vanadium content in the prepared ion storage material is 13.6 at%.
[0059] The ion storage membrane prepared in the above-mentioned embodiments and comparative examples is combined with an electrochromic polymer (e.g., the electrochromic polymer described in U.S. Patent No. 9975989) and an electrolyte (electrolyte layer described in U.S. Patent No. 0299932) to prepare an electrochromic device. The change of the unit area ion storage capacity of the prepared electrochromic device (100*100mm) with the number of charge and discharge cycles calculated under the control logic of 80°C high temperature, charge and discharge voltage of 1.0V, and charge and discharge time of 40s is as follows: Figure 1 As shown, the color change response time is Figure 2 shown.
[0060] The ratio of tetravalent vanadium to the total vanadium element in the ion storage materials described in the above embodiments and comparative examples was tested by X-ray photoelectron spectroscopy, and the vanadium 2p characteristic peak was peak-fitted, such as Figure 5 As shown, the characteristic peak at ~516.5eV is the peak of tetravalent vanadium, and the characteristic peak at ~517.6eV is the peak of pentavalent vanadium. The atomic ratio of V4+ = the integrated area of V4+ characteristic peak / (the total area of V4+ and V5+ characteristic peaks)
[0061] Depend on Figure 1 and Figure 2 The charge and discharge stability and color change response time of the electrochromic device corresponding to Examples 1-5 and Comparative Examples 1-2 shown in the figure show that the use of a second metal or non-metal precursor (such as titanium, niobium, zirconium, silicon, etc.) in a suitable proportion to dope vanadium oxide and undergo aging treatment shows that the color change speed is comparable to that of the vanadium oxide material, but the high-temperature charge and discharge stability of the vanadium oxide material can be greatly improved. In addition, the ion storage material of the present invention can be produced on a large scale by conventional precision coating methods.
[0062] The above description is only a preferred embodiment of the present invention and is not any formal or substantial limitation of the present invention. It should be pointed out that a person skilled in the art can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention.
Claims
1. A multi-metal carbon oxide ion storage layer material for an electrochromic device, characterized in that: The ion storage layer material is prepared by wet coating a multi-metal carbide precursor composition after aging, and the composition comprises a first metal oxide precursor, a second metal and / or non-metal oxide precursor and a polar solvent.
2. The ion storage layer material according to claim 1, characterized in that: The first metal oxide precursor is a vanadium oxide precursor, and the vanadium oxide precursor includes alkoxy vanadium oxide and / or alkoxy vanadium; The vanadium oxide precursor is selected from at least one of trimethoxy vanadium oxide (V), ethoxide vanadium (V), triethoxy vanadium oxide (V), triisopropoxy vanadium oxide (V), tri-n-butoxy vanadium oxide (V), tri-tert-butoxy vanadium oxide (V), isopropoxy acetylacetonate vanadium (V) (V(acac)(O-iPr)4, V(acac)2(O-iPr)3, V(acac)3(O-iPr)2, V(acac)4(O-iPr)), and vanadium (IV) oxide diacetylacetonate.
3. The ion storage layer material according to claim 1, characterized in that The second metal or non-metal oxide precursor is selected from at least one of a titanium oxide precursor, a niobium oxide precursor, a zirconium oxide precursor and a silicon oxide precursor.
4. The ion storage layer material according to claim 3, characterized in that The titanium oxide precursor is selected from at least one of tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate, acetylacetonato titanium and bis(acetylacetonato) diisopropyl titanate; The niobium oxide precursor is selected from at least one of niobium isopropoxide, niobium n-propoxide, niobium n-butoxide, niobium ethoxide and niobium oxalate; The zirconium oxide precursor is selected from at least one of tetrabutyl zirconate, tetraisopropyl zirconate, tetraethyl zirconate, zirconium acetate and zirconium acetylacetonate; The silicon oxide precursor is selected from at least one of alkoxy-containing silane, hydroxy-containing silane, mercapto-containing silane, epoxy-containing silane and fluorine-containing silane; The polar solvent is an alcohol solvent and / or a ketone solvent.
5. The ion storage layer material according to claim 4, characterized in that The polar solvent is selected from at least one of ethanol, isopropanol, n-butanol, sec-butanol and butanone.
6. The ion storage layer material according to claim 1, characterized in that The aging treatment comprises: stirring the prepared composition in a constant humidity environment with a humidity of 30-75Rh% at room temperature for 2-24 hours in an open state, then sealing the composition with a cover, and leaving the composition to stand at room temperature for 3-14 days.
7. The ion storage layer material according to claim 1, characterized in that The concentration of the precursor in the composition is 1-30 wt %.
8. The ion storage layer material according to claim 1, characterized in that The ion storage layer material includes one or more of titanium oxide, niobium oxide, zirconium oxide and silicon oxide doped with vanadium oxide or a multi-metal carbon oxide or a hydrate thereof.
9. The ion storage layer material according to claim 8, characterized in that The ion storage layer material includes but is not limited to at least one of the following multi-metal carbide oxides: Ti x1 V x2 O y C z nH2O, wherein the ratio (molar ratio) of x1 / x2 is 1:10 to 1:1; Nb x1 V x2 O y C z ●nH2O, where the ratio of x1 / x2 is 1:20 to 1:1; Zr x1 V x2 O y C z nH2O, where the ratio of x1 / x2 is 1:10 to 1:1; Si x1 V x2 O y C z ●nH2O, where the ratio of x1 / x2 is 1:15 to 1:2; Si x1 Ti x2 V x3 O y C z ●nH2O, where the ratio of x1 / x2 is 1:15 to 1:1, and the ratio of x2 / x3 is 1:10 to 1:1; In the above-mentioned polymetallic carbide, n is 0-3.
10. The ion storage layer material according to claim 7, characterized in that In the multi-metal carbon oxide, the atomic ratio of tetravalent vanadium to vanadium element is 10-70 at%.
11. The ion storage layer material according to claim 7, characterized in that The coating layer has a thickness of 20-300 nm, and the ion storage layer material exists in the coating layer in the form of nanoparticle accumulation with a particle size of 10-50 nm.
12. An electrochromic device, characterized in that: The ion storage layer material comprises the ion storage layer material as claimed in any one of claims 1 to 10.
13. The method for preparing the ion storage layer material according to any one of claims 1 to 10, characterized in that: include: Providing a multimetallic carbide precursor composition for preparing the ion storage layer material; The composition is aged and then coated on a conductive substrate to form a film, which is then subjected to a stepwise baking process to obtain a final multi-metal carbon oxide ion storage layer material.
14. The method of claim 12, wherein: The conductive substrate includes PET-ITO film, ITO conductive glass, PET-metal grid or PET-nanosilver wire film.
15. The method of claim 12, wherein: The coating and film forming includes coating and film forming by spin coating, screen printing, micro gravure coating or slit coating.
16. The method of claim 2, wherein the staged baking comprises two stages of baking: low temperature and high temperature; the low temperature baking is performed at a temperature of 30-50°C for 1-5 minutes, and the high temperature baking is performed at a temperature of 100-145°C for 2-60 minutes.
Citation Information
Patent Citations
miller
US299932A
Multicolored electrochromic polymer compositions and methods of making and using the same
US9975989B2